FAKTOR – FAKTOR YANG MEMPENGARUHI DAYA TARIK WISATA AIR TERJUN AEK MARTUA DI DESA TANGUN KECAMATAN BANGUN PURBA KABUPATEN ROKAN HULU PROVINSI RIAU - Habib Soleh; Syofia Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The research purpose to get know what the factor have effect to tourist attraction Aek Matua waterfall in Village Tangun, District Bangun Purba, Regency Rokan Hulu.The research use quantitative descriptive method to analyze the problem.The sample of this research are 30 tourist use accidental sampling technique. The data collected in this research are using observation, interview, questionnaire and documentation.According to the result of this research, the natural beauty became the most effect factor because natural condition is very goods. As evidenced by indicator are fulfilled like waterfall, forest and river’s beautys.Key word: tourist attraction, Aek Martua waterfall, Rokan Hulu